1981
DOI: 10.1080/00039896.1981.10667642
|View full text |Cite
|
Sign up to set email alerts
|

Household Pesticide Usage in the United States

Abstract: A total of 10,000 U.S. households in 25 standard metropolitan statistical areas and 25 counties were included in the United States. More than 8,200 households granted an interview. Nine of every ten households in the United States used some types of pesticide in their house, garden, or yard. Households in the southeastern United States used the most pesticides. Although more than 500 different pesticide formulations were used by the sampled households, 15 pesticides accounted for 65.5% of all pesticides report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 1 publication
3
30
0
Order By: Relevance
“…Mostly, previous studies covered a wider range of pesticides besides insecticides, for example, herbicides, rodenticides, disinfectants, and insect repellents, and may have considered usage over longer or shorter periods. For example, Savage et al (1981) reported that in the EPA region IX where California is located, 82.5% and 62.2% of households had ever used pesticides in the house and yard respectively, during late 1970s. Adgate et al (2000) collected residential pesticide inventory data in 1997 from households with children age 3-12 years in Minnesota, and reported a comparable prevalence of pesticide use for 88% of households during the past year.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, previous studies covered a wider range of pesticides besides insecticides, for example, herbicides, rodenticides, disinfectants, and insect repellents, and may have considered usage over longer or shorter periods. For example, Savage et al (1981) reported that in the EPA region IX where California is located, 82.5% and 62.2% of households had ever used pesticides in the house and yard respectively, during late 1970s. Adgate et al (2000) collected residential pesticide inventory data in 1997 from households with children age 3-12 years in Minnesota, and reported a comparable prevalence of pesticide use for 88% of households during the past year.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…Several nationaland regional-scale studies have been conducted, demonstrating that up to 90% of US households used pesticides in their house, garden, or yard, and more than half of the products applied were insecticides (Savage et al, 1981;Davis et al, 1992;Whitmore et al, 1994;Adgate et al, 2000;Colt et al, 2004). However, estimating human exposures from residential insecticide applications has been a challenge because of the lack of detailed information on the manner and patterns of applications and exposure related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was derived from the baseline questionnaire used in the National Human Exposure Assessment Survey (Lioy et al, 2000), and contained additional questions about pesticide use patterns drawn from NOPES (Whitmore et al, 1994) and the National Home and Garden Pesticide Use Survey (Savage et al, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Regular use of pesticides to control household pests is wide spread (Savage et al, 1981;Davis et al, 1992). The EPA Non-Occupational Pesticide Exposure Study (NOPES) found elevated levels of pesticide residues from household use in nearly all houses sampled (Whitmore et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although nonchemical alternative methods of control exist, these chemical products provide an easy and effective solution (Grieshop et al, 1992). Evidence of their success is that over 90% of households in the USA and UK use them (Savage et al, 1981;Grieshop and Stiles, 1989;Davis et al, 1992;Grieshop et al, 1992;Adgate et al, 2000;Grey, 2003). More recent or larger surveys may suggest this figure is declining in the USA to about 75% (Whitmore et al, 1992;Donaldson et al, 2002;Berkowitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%